HelpWave: an integrated web centred system - Cunha, António (2015)
In developed societies populations are aging. Facing the global slump states are reducing expenses bringing crisis to health care systems. Solutions to decrease costs are needed. Within ICT, smartphones’ features can help provide personalised health and care services that meet individual needs. There is a huge rise of applications that effectively help people but they act independently, each one for a certain purpose. In this paper we propose the HelpWave system, a cloud-centred architecture information system that integrates data from the users’ smartphones APPs. Conceived as a social care network its aim is to reinforce connection between caregivers and carereceiver as for instance, older people.